Determinant Factor Analysis of Financial Technology Adoption Among Halal Sector Microenterprises in Indonesia - Devi, Abrista; Firmansyah, Irman; Yuniarto, Arif Sapta; Hamid, Baharom Abdul; Nawawi, M Kholil (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
This study offers an empirical analysis of the factors that influence the customer attitudes towards the adoption of Financial Technology services within the Micro, Small, and Medium Enterprises (MSMEs) sector. Using Survey method, a total of 240 respondents from MSMEs were included in the sample for this study. These respondents were selected from 16 different areas located in five typical provinces in Indonesia, namely Aceh, West Sumatera, Jakarta, West Java, and East Java. This research investigates the impact of several key factors on the consumer attitudes of MSMEs towards the adoption of FinTech. These factors include Perceived Ease of Use, Digital Literacy, Risk Perception, Infrastructure, Entrepreneurial Spirit, and Perceived Usefulness. This paper utilized the Structural Equation Modelling (SEM) technique to analyse various measurement, observations, and a hybrid model. The results of the study suggest that within the specific domain of halal sector MSMEs in Indonesia, there is no significant impact of parameters such as digital finance literacy, perceived risk, and perceived utility on the adoption of digital financial services. Nevertheless, it has been observed that the perceived ease of use, the presence of adequate infrastructure, and the presence of an entrepreneurial mindset have been found to have a positive and statistically significant influence on the adoption of financial technology services among MSMEs. This study also offers theoretical and practical implications for key stakeholders seeking to enhance the utilization of financial technology services among MSMEs in Indonesia